Usnic acid based thiazole-hydrazones as multi-targeting inhibitors of a wide spectrum of SARS-CoV-2 viruses - Yarovaya, Olga I; Filimonov, Aleksandr S; Baev, Dmitriy S; Borisevich, Sophia S; Chirkova, Varvara Yu; Zaykovskaya, Anna V; Mordvinova, Ekaterina D; Belenkaya, Svetlana V; Shcherbakov, Dmitriy N; Luzina, Olga A; Pyankov, Oleg V; Salakhutdinov, Nariman F (New journal of chemistry, 2023)
Although the Covid-19 pandemic is officially over and the spread of coronavirus infection is no longer considered an international emergency, the virus continues to persist in the population, supporting the process of mutagenesis, which may lead to the emergence of more dangerous variants that can cause new outbreaks in the future. Therefore, the search for new effective drugs against the SARS-CoV-2 virus and other coronaviruses with a wide spectrum of activity remains an urgent task of medicinal chemistry. We synthesized a set of thiazolo-hydrazones based on (+)- and (−)-usnic acid and studied their ability to inhibit the main viral protease of the SARS-CoV-2 virus. It was shown that 9 out of 36 agents exhibit antiprotease activity in the range from 13 to 27 μM. The kinetic parameters of the four most active compounds were studied and molecular modeling of the possible interaction of these compounds with the active site of the main protease was carried out. Using six different strains (Wuhan, Delta, and four Omicron lines) of the SARS-CoV-2 virus, the antiviral activity of selected leader compounds was studied and it was shown that agent (+)-7a with a furan fragment has a pronounced antiviral activity against all strains. Additionally, the ability of the leading compounds to influence the stage of virus entry was studied, for which the activity of the compounds against the pseudoviral system with S glycoprotein on its surface was studied, as well as the ability to inhibit the interaction of recombinant ACE2 receptors with the RBD domain of the S protein by ELISA testing. It was found that the leading compounds are able to effectively inhibit pseudoviral particles without affecting the interaction of ACE2 and RBD. In order to search for a possible binding site for the leading compounds on the surface of the S-protein, molecular modeling was carried out. The N-terminal domain of the S protein was considered as a potential biological target, and it was found that the agents probably bind to the biliverdin site of the surface glycoprotein. Thus, we have identified new usnic acid derivatives that are active against a wide range of strains of the SARS-CoV-2 virus and have multi-targeting effects. We have identified new usnic acid derivatives that are active against a wide range of strains of the SARS-CoV-2 virus and have multi-targeting effects.